Preparation method of dry-method pole piece, dry-method pole piece and application of dry-method pole piece in battery

By intensively refining and hot-pressing the dry electrode material, the problem of electrode material agglomeration after fibrosis is solved, the uniformity and efficiency of the electrode sheet are achieved, and the overall performance of the battery is improved.

CN119581473APending Publication Date: 2025-03-07CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411671322.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

During the preparation of dry electrodes, the fibrated electrode materials are prone to particle agglomeration, resulting in uneven powder and discontinuous calendering process, which reduces the overall performance of the battery.

Method used

By intensively refining the fibrotic electrode sheet powder, adding a refining agent to homogenize it, and then hot pressing and compounding treatment are carried out to obtain a uniform and efficient dry electrode sheet.

Benefits of technology

The uniform dispersion and efficient film formation of the electrode sheet material are achieved, the Coulomb efficiency and cycle stability of the battery are improved, the process flow is simplified, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581473A_ABST
    Figure CN119581473A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a dry-method pole piece, the dry-method pole piece and application of the dry-method pole piece in a battery, and the preparation method comprises the following steps: carrying out banburying treatment on fiberized pole piece powder, and adding a banburying agent to obtain homogenized pole piece powder; performing hot press molding on the homogenized pole piece powder to obtain a dry membrane; and compounding the dry-method diaphragm on a current collector through hot pressing to obtain the dry-method pole piece. The dry-method pole piece preparation method is simple and efficient in process, and on the basis of a universal mixing process, the internal mixing agent is added in the internal mixing process, so that dispersions are micronized and homogenized, the problem of particle aggregation is solved, and uniform substance dispersion, uniform film forming thickness and excellent pole piece consistency are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material preparation, and in particular relates to a method for preparing a dry-process electrode sheet, the dry-process electrode sheet and the application of the dry-process electrode sheet in a battery. Background Art

[0002] Dry cathode technology is considered to be a lithium battery manufacturing technology with great potential. It can better meet the market demand for green environmental protection, high efficiency and low consumption, and promote the sustainable development of the lithium battery industry.

[0003] At present, the preparation of battery positive electrode materials usually adopts a wet process, that is, the active material, conductive agent and binder are mixed in a solvent to form a slurry, which is then coated on the current collector and dried. However, there are some problems with the wet process. For example, the use of solvents will cause environmental pollution and safety hazards, and the recovery and treatment of solvents increase production costs. At the same time, the drying process in the wet process consumes a lot of energy, which affects production efficiency. In order to solve these problems, dry positive electrode technology came into being. The dry positive electrode process does not require the use of solvents. The active material, conductive agent and binder are directly coated on the current collector by mechanical pressing, rolling or other solid-state processing methods.

[0004] Fibrillation is a common step in the preparation of dry electrodes, which helps to improve the structural properties of the electrodes, such as conductivity and mechanical properties.

[0005] However, after the electrode material is fiberized, particles may agglomerate due to the mutual attraction between fibers or electrostatic effects. This agglomeration phenomenon is particularly significant in the powder state, causing the powder to present an uneven block structure. Particle agglomeration may also lead to discontinuities in the calendering process, that is, the formation of voids between particles or discontinuous conductivity paths in the film, which will reduce the overall performance of the battery, such as the Coulomb efficiency and cycle stability of the battery, which will bring some challenges in practical applications. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a dry-process electrode.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a dry electrode, comprising:

[0010] The fiberized electrode powder is subjected to internal mixing treatment, and an internal mixing agent is added to obtain a homogenized electrode powder;

[0011] The homogenized electrode powder is hot pressed to obtain a dry-process membrane;

[0012] The dry-process membrane is hot-pressed and composited onto the current collector to obtain a dry-process electrode.

[0013] As a preferred embodiment of the preparation method of the present invention, the mixing agent includes one or more of ethanol, propanol, isopropanol, propylene glycol, acetone, benzene, ether and carbon tetrachloride.

[0014] As a preferred solution of the preparation method of the present invention, the mass percentage of the mixing agent in the fiberized pole piece powder is 1 to 8 wt %.

[0015] As a preferred embodiment of the preparation method of the present invention, the preparation method of the fiberized electrode powder comprises:

[0016] The electrode active material, the binder and the conductive agent are mixed evenly to obtain a mixed powder;

[0017] Heating and drying to obtain heated and dried powder;

[0018] The heated and dried powder is subjected to air flow grinding treatment to obtain a fiberized mixed powder.

[0019] As a preferred embodiment of the preparation method of the present invention, the electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel-cobalt-manganese ternary material, carbon fluoride and lithium nickel-cobalt-aluminum oxide;

[0020] The binder includes a fiberizable polymer, polyacrylate, polyvinyl alcohol, carboxymethyl cellulose, polyimide and polyvinyl ester polyvinylidene fluoride, wherein the fiberizable polymer is one or more of sulfonated tetrafluoroethylene, polytetrafluoroethylene, nylon, cellulose, high-density polyethylene or a combination thereof;

[0021] The conductive agent includes at least one of acetylene black, carbon fiber, carbon nanotube, Ketjen black or graphene;

[0022] Wherein, based on the total mass of the electrode active material, the binder and the conductive agent, the electrode active material accounts for 85-98%, the binder accounts for 0.2-10%, and the conductive agent accounts for 0-20%.

[0023] As a preferred embodiment of the preparation method of the present invention, the air flow grinding treatment includes pulverizing by an air flow mill, wherein the feeding screw frequency of the air flow mill is 0.1Hz~100Hz, the grading turbine frequency of the air flow mill is 0.1Hz~100Hz, the temperature is 80℃~280℃, the gas pressure of the gas crushing chamber of the air flow mill is 0.1MPa~1MPa, and the gas feed amount of the air flow mill is 0.1m 3 / min~10m 3 / min, and the fibrosis time is 1min~600min.

[0024] As a preferred embodiment of the preparation method of the present invention, the internal mixing treatment includes micronizing and homogenizing the dispersed material by an internal mixer, wherein the linear speed of the stirring paddle of the internal mixer is 30m / s to 70m / s.

[0025] As a preferred embodiment of the preparation method of the present invention, the hot pressing process has a treatment temperature of 100°C to 150°C and a pressure of 5T to 10T.

[0026] Another object of the present invention is to overcome the deficiencies in the prior art and provide a pole piece.

[0027] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a pole piece in the preparation of a battery, wherein the battery is one or more of a lithium battery, a sodium battery, a magnesium battery, a zinc battery, an iron battery or a carbon fluoride battery.

[0028] Beneficial effects of the present invention:

[0029] (1) The dry-process electrode preparation method of the present invention is simple and efficient. On the basis of the general mixing process, a mixing agent is added during the mixing process to make the dispersed material micronized and uniform, solve the problem of particle agglomeration, achieve uniform material dispersion, uniform film thickness, and excellent electrode consistency.

[0030] (2) The present invention first performs a fiberization treatment on the premixed powder to improve the dispersion uniformity of the conductive agent and the binder therein. During the fiberization process, the temperature is controlled at no less than the glass transition temperature of the fiberizable polymer, thereby significantly enhancing the fiberization ability of the binder and making it easier to achieve fiberization.

[0031] (3) The compaction density, environmental protection, energy efficiency and production of the diaphragm in the dry-process electrode prepared by the present invention are all improved, which is conducive to wide application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0033] Figure 1 The figure is a flow chart of the method for preparing a dry electrode in an embodiment of the present invention.

[0034] Figure 2 The figures are actual pictures of the powders prepared in the examples of the present invention, wherein (a) is the actual picture of the powders without the addition of the internal mixing agent, and (b) and (c) are the actual pictures of the powders with the addition of the internal mixing agent.

[0035] Figure 3 1 and 2 are the appearances of the rolled-up electrode membranes in the embodiments of the present invention, wherein (a) is the appearance of the rolled-up electrode membrane without the addition of a mixing agent, and (b) is the appearance of the rolled-up electrode membrane with the addition of a mixing agent.

[0036] Figure 4 1 and 2 are scanning electron microscope (SEM) images of dry-process electrodes in the embodiments of the present invention, wherein (a) is a scanning electron microscope (SEM) image of the dry-process electrode prepared in Example 1, and (b) is a scanning electron microscope (SEM) image of the dry-process electrode prepared in Example 2. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] The diaphragm used in the present invention is a polyethylene diaphragm purchased from CLUDE, model MA-EN-SE-0007, with a thickness of 12 μm.

[0041] The negative electrode lithium sheet used in the present invention is purchased from Zhongneng Lithium Industry, and has a thickness of 300 μm and a diameter of 14 mm.

[0042] The NCM622 powder used in the present invention is purchased from CLUDE, with a gram capacity of 176 mAh / g.

[0043] The polytetrafluoroethylene used in the present invention is purchased from CLUDE, model MA-EN-BI-0024, with a density of 2.16 g / cm3.

[0044] The conductive agent used in the present invention is purchased from CLUDE, model MA-EN-CO-000503.

[0045] The electrolyte used in the present invention is 1M LiPF6 in DMC:EC=1:1Vol%, purchased from Duoduo Electrolyte, and the added amount is 100μL.

[0046] Unless otherwise specified, the raw materials used in the present invention are commonly available in the market.

[0047] Example 1

[0048] (1) Using a stirring mixer, the ternary positive electrode NCM622, the conductive agent SP (conductive carbon black) and the binder PTFE are first mixed uniformly at a rotation speed of 700 rpm and a mixing time of 120 min; wherein the mass ratio of the ternary positive electrode NCM622, SP and PTFE is 95:2.5:2.5, and the electrode powder is obtained after stirring and mixing.

[0049] (2) The electrode powder material is placed in a vacuum drying oven and heated and dried at a temperature of 120° C. for 500 min to obtain a heated and dried powder.

[0050] (3) The dried powder was put into a jet mill in an amount of 2.5 kg per batch for fiberization. The feeding screw frequency was 50 Hz, the classification turbine frequency was 25 Hz, the grinding chamber gas pressure was 0.5 MPa, and the intake flow rate was 5 m 3 / min, the crushing time is 60min, the fiberizing treatment temperature is 120℃, the time is 90min, and then the material is collected from the cyclone collector to obtain fiberized pole piece powder.

[0051] (4) The above-mentioned fiberized electrode powder is passed through an internal mixer to be dispersed into micronized particles and homogenized. The linear speed of the stirring paddle of the internal mixer is 50 m / s, and the internal mixer time is 180 min.

[0052] (5) The electrode powder after heating and drying is formed into a film by a dry hot roller press, with a roller pressure of 3T, a roller gap of 45μm, a roller temperature of 120°C, a roller line speed of 1m / min, and a roller gap width of 290μm, to obtain a self-supporting dry film with a thickness of 430μm. The dry film coil is obtained by continuous winding, and the thickness of the film is reduced to 400μm, with a surface density of 78.1mg / cm 2 , compacted density is 2.43g / cm 3 .

[0053] (6) The dry film is pressed onto the current collector by a dry hot roller press to obtain a dry electrode, wherein the roller pressure is 8T, the roller temperature is 130°C, and the roller line speed is 1m / min. A single-sided electrode is produced, and the thickness of the electrode is 330±10μm and the compaction density of the electrode is 3.11g / cm 3 .

[0054] See the preparation process flow chart for Figure 1 .

[0055] Example 2

[0056] (1) Using a stirring mixer, the ternary positive electrode NCM622, the conductive agent SP (conductive carbon black) and the binder PTFE are first mixed uniformly at a rotation speed of 700 rpm and a mixing time of 120 min; wherein the mass ratio of the ternary positive electrode NCM622, SP and PTFE is 95:2.5:2.5, and the electrode powder is obtained after stirring and mixing.

[0057] (2) The electrode powder material is placed in a vacuum drying oven and heated and dried at a temperature of 120° C. for 500 min to obtain a heated and dried powder.

[0058] (3) The dried powder was put into a jet mill in an amount of 2.5 kg per batch for fiberization. The feeding screw frequency was 50 Hz, the classification turbine frequency was 25 Hz, the grinding chamber gas pressure was 0.5 MPa, and the intake flow rate was 5 m 3 / min, the crushing time is 60min, the fiberizing treatment temperature is 120℃, the time is 90min, and then the material is collected from the cyclone collector to obtain fiberized pole piece powder.

[0059] (4) The above-mentioned fiberized electrode powder is dispersed and micronized and homogenized by an internal mixer, wherein the linear speed of the stirring paddle of the internal mixer is 50 m / s and the internal mixing time is 180 min; wherein, an internal mixing agent is added, and the internal mixing agent is acetone, and the proportion of the internal mixing agent added is 5wt% of the fiberized electrode powder.

[0060] (5) The electrode powder after heating and drying is formed into a film by a dry hot roller press, with a roller pressure of 3T, a roller gap of 45μm, a roller temperature of 120°C, a roller line speed of 1m / min, and a roller gap width of 290μm, to obtain a self-supporting dry film with a thickness of 340μm. The dry film coil is obtained by continuous winding, and the thickness of the film is reduced to 290μm, with a surface density of 89.2mg / cm 2 , compacted density is 2.96g / cm 3 .

[0061] (6) The dry film is pressed onto the current collector by a dry hot roller press to obtain a dry electrode, wherein the roller pressure is 8T, the roller temperature is 130°C, and the roller line speed is 1m / min. A single-sided electrode is produced, and the thickness of the electrode is 290±10μm and the compaction density of the electrode is 3.11g / cm 3 .

[0062] Example 3

[0063] (1) Using a stirring mixer, the ternary positive electrode NCM622, the conductive agent SP (conductive carbon black) and the binder PTFE are first mixed uniformly at a rotation speed of 700 rpm and a mixing time of 120 min; wherein the mass ratio of the ternary positive electrode NCM622, SP and PTFE is 95:2.5:2.5, and the electrode powder is obtained after stirring and mixing.

[0064] (2) The electrode powder material is placed in a vacuum drying oven and heated and dried at a temperature of 120° C. for 500 min to obtain a heated and dried powder.

[0065] (3) The dried powder was put into a jet mill in an amount of 2.5 kg per batch for fiberization. The feeding screw frequency was 50 Hz, the classification turbine frequency was 25 Hz, the grinding chamber gas pressure was 0.5 MPa, and the intake flow rate was 5 m 3 / min, the crushing time is 60min, the fiberizing treatment temperature is 120℃, the time is 90min, and then the material is collected from the cyclone collector to obtain fiberized pole piece powder.

[0066] (4) The above-mentioned fiberized electrode powder is dispersed in a micronized and homogenized material by a mixer, wherein the linear speed of the stirring paddle of the mixer is 50 m / s and the mixing time is 180 min; wherein a mixing agent is added, the mixing agent is isopropanol, and the mixing agent addition ratio is 5wt% of the fiberized electrode powder.

[0067] (5) The electrode powder after heating and drying is formed into a film by a dry hot roller press, with a roller pressure of 3T, a roller gap of 45μm, a roller temperature of 120°C, a roller line speed of 1m / min, and a roller gap width of 290μm, to obtain a self-supporting dry film with a thickness of 335μm. The dry film coil is obtained by continuous winding, and the thickness of the film is reduced to 290μm, with a surface density of 89.4mg / cm 2 The thickness of the pole piece is 290±10μm and the compaction density is 2.96g / cm 3 .

[0068] (6) The dry film is pressed onto the current collector by a dry hot roller press to obtain a dry electrode, wherein the roller pressure is 8T, the roller temperature is 130°C, and the roller line speed is 1m / min. A single-sided electrode is produced, and the thickness of the electrode is 290±10μm and the compaction density of the electrode is 3.14g / cm 3 .

[0069] The actual picture of the powder obtained in Example 1 is shown in Figure 2 (a), the actual picture of the powder obtained in Example 2 is shown in Figure 2 (b), the actual picture of the powder obtained in Example 3 is shown in Figure 2 (c) It can be seen that after adding the internal mixing agent, the dispersion is micronized and homogenized, solving the problem of particle agglomeration. Therefore, adding an appropriate internal mixing agent is of great significance for improving the dispersion of particles and increasing the uniformity of particle size, which is helpful for subsequent film formation.

[0070] The appearance of the electrode membrane obtained in Example 1 is shown in Figure 3 (a) The appearance of the electrode membrane prepared in Example 2 is shown in Figure 3 (b) It can be seen that the powder film formed by using the internal mixing agent is more uniform, and the film surface should not have obvious unevenness, bubbles, scratches or other defects. However, the film formed by the powder without the internal mixing agent has more wrinkles.

[0071] Comparative Example 1

[0072] This comparative example provides a method for preparing a wet-process electrode, and the preparation method is as follows:

[0073] (1) Using a stirring mixer, the ternary positive electrode NCM622, the conductive agent SP (conductive carbon black) and the binder PVDF are first mixed uniformly at a rotation speed of 700 rpm and a mixing time of 120 min; wherein the mass ratio of the ternary positive electrode NCM622, SP and PTFE is 95:2.5:2.5, and the electrode powder is obtained after stirring and mixing.

[0074] (2) The electrode powder material is placed in a vacuum drying oven and heated and dried at a temperature of 120° C. for 500 min to obtain a heated and dried powder.

[0075] (3) The heated and dried powder was added with N-methylpyrrolidone (NMP) through a stirring mixer at a rotation speed of 700 rpm and a mixing time of 60 min to obtain a wet electrode slurry.

[0076] (4) The wet electrode slurry is applied to the current collector by an automatic coating machine, wherein the coating thickness of the automatic coating machine is 500 μm and the line speed is 0.5 m / min to produce a single-sided electrode sheet with an area density of 0.0194 g / cm 2.

[0077] Performance test in the embodiment of the present invention:

[0078] (1) Scanning electron microscopy (SEM) was performed on the dry-process electrodes obtained in Example 1 and Example 2 to obtain Figure 4 (a) and Figure 2 (b).

[0079] Depend on Figure 4 (a) It can be seen that without the addition of a mixing agent, there is an obvious agglomeration of particles in the material, which indicates that without the help of a mixing agent, the interaction between the particles is strong, causing them to tend to aggregate together to form larger agglomerates rather than being evenly dispersed in the matrix.

[0080] Depend on Figure 4 (b) It can be seen that after treatment, the dispersion has been micronized and homogenized, and there is no particle agglomeration. Therefore, adding appropriate mixing agent is of great significance to improving the dispersion of particles and improving the overall performance of the electrode.

[0081] Test methods for dry electrode and wet electrode buckle charge and discharge test:

[0082] The equipment uses a blue electric tester to place the electrode pieces in a vacuum drying oven and heat and dry them for 8 hours (vacuum degree 0.1MPa, temperature 80℃). After drying, the positive electrode pieces are cut into discs with a diameter of 12mm, and the negative electrode lithium pieces are cut into discs with a diameter of 14mm. Each electrode piece is compacted and weighed.

[0083] Then assemble the positive electrode, negative electrode, separator, gasket and spring into a CR2025 button battery and start testing.

[0084] Testing steps for dry electrode and wet electrode:

[0085] (1) Leave to stand for 6 hours;

[0086] (2) 0.05C constant current charging, cut-off voltage 4.3V;

[0087] (3) Leave to stand for 0.5 h;

[0088] (4) 0.05C constant current discharge, cut-off voltage 3V;

[0089] (5) Leave to stand for 0.5 h;

[0090] (6) 0.1C constant current and constant voltage charging, cut-off voltage 4.3V, cut-off current 0.05C;

[0091] (7) Leave to stand for 0.5 h;

[0092] (8) 0.1C constant current discharge, cut-off voltage 3V;

[0093] (9) Leave to stand for 0.5 h;

[0094] (10) Steps (2) to (9) are repeated 300 times.

[0095] The test results of the prepared electrode are shown in Table 1.

[0096] Table 1

[0097]

[0098] From Table 1, the first-cycle efficiency of Example 2 is the highest, which is 96.88%, while that of Example 1, Example 3 and Comparative Example 1 are 93.31%, 96.86% and 96.55% respectively; the median voltage of Example 2 is the highest, which is 3.7674V, while that of Example 1, Example 3 and Comparative Example 1 are 3.7051V, 3.7669V and 3.7428V respectively; the reversible capacity of Example 2 is the maximum, which is 172.8mAh / g, while that of Example 1, Example 3 and Comparative Example 1 are 140.5mAh / g, 172.5mAh / g and 154.1mAh / g respectively, indicating that the dry-process electrode sheet using a mixing agent can significantly improve the overall performance of the battery.

[0099] The comparison of electrode membrane thickness without mixing agent and with mixing agent is shown in Table 2.

[0100] Table 2

[0101]

[0102]

[0103] As can be seen from Table 2, the electrode sheets after adding the internal mixing agent in Examples 2 and 3 are thinner than the electrode sheet without the internal mixing agent in Example 1. Because the internal mixing agent was not added in the preparation or subsequent treatment process of Example 1, the electrode sheet material was unevenly distributed, thus forming stress in the electrode sheet. After the rolling, the internal stress of the electrode sheet was released, causing the material to expand and the thickness of the electrode sheet to increase. This phenomenon not only affects the physical size of the electrode sheet, but also may have a certain impact on its electrochemical performance.

[0104] The addition of the mixing agent in Example 2 and Example 3 can effectively improve the compatibility and dispersibility between the materials, so that various active substances and conductive agents can be more evenly distributed in the pole piece matrix. This uniform distribution not only helps to improve the overall performance of the pole piece, such as electrochemical performance and mechanical strength, but also reduces the internal stress of the pole piece, because the addition of the mixing agent reduces the agglomeration phenomenon between particles. This change is of great significance for improving the energy density and cycle stability of the battery.

[0105] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a dry electrode, characterized in that: include, The fiberized electrode powder is subjected to internal mixing treatment, and an internal mixing agent is added to obtain a homogenized electrode powder; The homogenized electrode powder is hot pressed to obtain a dry-process membrane; The dry-process membrane is hot-pressed and composited onto the current collector to obtain a dry-process electrode.

2. The method according to claim 1, wherein: The mixing agent includes one or more of ethanol, propanol, isopropanol, propylene glycol, acetone, benzene, ether and carbon tetrachloride.

3. The preparation method according to claim 1 or 2, characterized in that: The mass percentage of the mixing agent in the fiberized pole piece powder is 1-8wt%.

4. The preparation method according to claim 3, characterized in that: The method for preparing the fiberized pole piece powder comprises: The electrode active material, the binder and the conductive agent are mixed evenly to obtain a mixed powder; Heating and drying to obtain heated and dried powder; The heated and dried powder is subjected to air flow grinding treatment to obtain a fiberized mixed powder.

5. The preparation method according to claim 4, characterized in that: The electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel-cobalt-manganese ternary material, carbon fluoride and lithium nickel-cobalt-aluminum oxide; The binder includes a fiberizable polymer, polyacrylate, polyvinyl alcohol, carboxymethyl cellulose, polyimide and polyvinyl ester polyvinylidene fluoride, wherein the fiberizable polymer is one or more of sulfonated tetrafluoroethylene, polytetrafluoroethylene, nylon, cellulose, high-density polyethylene or a combination thereof; The conductive agent includes at least one of acetylene black, carbon fiber, carbon nanotube, Ketjen black or graphene; Wherein, based on the total mass of the electrode active material, the binder and the conductive agent, the electrode active material accounts for 85-98%, the binder accounts for 0.2-10%, and the conductive agent accounts for 0-20%.

6. The preparation method according to claim 5, characterized in that: The air flow grinding process includes grinding by an air flow mill, wherein the feeding screw frequency of the air flow mill is 0.1 Hz to 100 Hz, the classification turbine frequency of the air flow mill is 0.1 Hz to 100 Hz, the temperature is 80° C. to 280° C., the gas pressure of the gas crushing chamber of the air flow mill is 0.1 MPa to 1 MPa, and the gas feed amount of the air flow mill is 0.1 m 3 / min~10m 3 / min, and the fibrosis time is 1min~600min.

7. The preparation method according to any one of claims 1, 5 or 6, characterized in that: The internal mixing treatment includes micronizing and homogenizing the dispersed material by an internal mixer, wherein the linear speed of the stirring paddle of the internal mixer is 30 m / s to 70 m / s.

8. The preparation method according to claim 7, characterized in that: The hot pressing process has a processing temperature of 100° C. to 150° C. and a pressure of 5T to 10T.

9. A pole piece obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the pole piece according to claim 9 in preparing a battery, characterized in that: The battery is one or more of a lithium battery, a sodium battery, a magnesium battery, a zinc battery, an iron battery or a carbon fluoride battery.